Electricity consumption and manufacturing sector productivity in Nigeria: An ARDL-bounds testing approach - Danmaraya, Ismail Aliyu; Hassan, Sallahuddin (EconJournals, 2016)
This paper employs the Autoregressive Distributed Lag (ARDL) technique to provide evidence of long run and short run relationship, as well as the causality between manufacturing productivity and electricity consumption in Nigeria for the period 1980–2013. When electricity consumption, capital formation and manufacturing productivity are applied as the dependent variable(s), the bounds test provides a proof of cointegration among electricity consumption, manufacturing productivity, and capital. Similarly, the findings demonstrated bidirectional causality between manufacturing productivity and energy consumption. Nigeria is along this line an electricity reliant nation. It is likewise a nation in which electricity consumption is rising with the manufacturing productivity. This demonstrates that electricity is a powerful determinant of manufacturing performance in Nigeria; accordingly, policy on energy should guarantee that electricity creates less negative effects on manufacturing productivity.